Self-concept and Ego Development in Deaf Adolescents A Comparative Study - van Gent, Tiejo (Journal of Deaf Studies and Deaf Education, 2012)
Self-concept and ego development, two intertwined aspects of self-indicating well-being and social-cognitive maturation, respectively, were examined in a representative sample of deaf adolescents of normal intelligence (N= 68), using translated and adapted versions of Harter’s (1988,Manual for the self-perception profile for adolescents. Denver, CO: University of Denver) multidimensional measure of self-concept and Loevinger’s (1998,Technical foundations for measuring ego development. Mahwah, NJ: Lawrence Erlbaum) measure of ego development. Compared to hearing norm groups, deaf adolescents showed lower levels of self-perceived social acceptance, close friendships and ego development and higher physical appearance. Hierarchical multiple regression analyses controlling for sociodemographic variables showed positive associations of global self-worth with support for signing during childhood and quality of parent-child communication and of ego development with attending a regular school. Cluster analysis identified three social competence profiles: uniformly low competence, uniformly high competence, and low social acceptance with high physical appearance. Cluster membership was associated with school type, ego development, and (past) neurological disorder. The results are discussed in reference to interventions aimed at the well-being of deaf youth.